Normal and tangential geodesic deformations of the surfaces of revolution - Fedchenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study special infinitesimal geodesic deformations of the surfaces of revolution in the Euclidean space E^3.